Development of Professional Ethics and Aesthetics E-Modules Based on Problem Based Learning to Improve Students' Critical Thinking Ability - Silvia, Febri; Astuti, Murni; Dewi, Siska Miga (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
Most students of the Department of Cosmetology and Beauty (TRK) Faculty of Tourism and Hospitality (FPP) Universitas Negeri Padang (UNP) are still unable to think critically in lectures, especially in analyzing problems related to the profession in the field of cosmetology and beauty. In addition, based on the explanation from the supporting lecturers, in Professional Ethics and Aesthetics lectures there are limited learning resources that can support students' critical thinking skills. The purpose of this research is to produce E-modules of Professional Ethics and Aesthetics based on Problem Based Learning that are appropriate, effective, and practical. Data collection in this study used validation questionnaires, critical thinking questions, and response questionnaires from students. The research method used is Research and Development. The data analysis technique used is descriptive quantitative and N-gain scores. The results showed that the average percentage of e-module feasibility was 94%, so it was included in the feasible category with a little revision. The effectiveness of the E-module in improving critical thinking skills is quite effective with an average percentage of 62.80 % and an N-gain score of 0.67. While the Practicality of the E-module shows a percentage of 90% with practical criteria.